A Three-Decade “Kuhnian” History of the Antebellum Puzzle: Explaining the shrinking of the US population at the onset of modern economic growth - John Komlos (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
In 1979, when anthropometric history was still in its infancy, Robert Fogel and collaborators reported that the height of the US male white population began to decline quite unexpectedly around the birth cohorts of 1830. This was quite a conundrum on account of the fact that according to conventional economic theory nutritional status was not expected to diminish at the outset of modern economic growth, i.e., at a time when incomes were growing robustly. Although many hypotheses were offered, not until 1987 was the comprehensive solution to the puzzle offered that the height decline was due primarily to a decline in food consumption: agricultural productivity did not keep pace with rapid population growth and urbanization. However, it took a third of a century for a Kuhnian paradigm shift to occur until most of the participants in the debate accepted the model elucidated by Komlos in 1987.
urn:nbn:de:bvb:19-epub-12758-4
Keywords: B20; B25; N00; 330; Anthropometric history; Heights; Thomas Kuhn; Paradigm shift; USA; Antebellum Puzzle; Living Standards; Biologische Daten; Wirtschaftswachstum; Industrialisierung; Sozialforschung; Wirtschaftsgeschichte; Dogmengeschichte; USA